Study on Social and Temperament Dimensions of Adolescents : A Gender and Socioeconomic Analysis - Kewal Krishan; Dr. Pawan Kumar; Dr. Ram Singh (International Journal of Scientific Research in Humanities and Social Sciences, 2025)
This paper explores the social experiences and temperament dimensions of adolescents across various sociometric groups, with a focus on gender and socioeconomic status. Using data collected from 500 adolescent boys and girls, this study analyzes feelings of neglect, rejection, isolation, and the temperament dimensions that define adolescents’ social interactions. Through descriptive statistics, we investigate how these social experiences differ across gender and socioeconomic groups. Hypothesis testing further delves into the significant differences in academic achievement and temperament across genders and socioeconomic statuses, providing evidence for targeted interventions to address social and academic challenges faced by adolescents.